PENGARUH LATIHAN DRIBBLING BERANTING TERHADAP KEMAMPUAN DRIBBLE PERMAINAN BOLA BASKET PADA TIM BASKET PUTRA SMP NEGERI 6 PEKANBARU - Zul Idham; Ramadi Ramadi; Zainur Zainur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is that the ability of Driblling Basketball is still low. It can be seen from various matches and it is one of the factor the team lost at several matches. This type of research is a type of experimental research which aims to see the effect of the form of training. The population in this research is the male basketball team of SMP N 6 Pekanbaru, which are 12 people. The sampling technique is by using total sampling, where all the total population is sampled. The purpose of this research is to look at the effect of berating dribbling exercises on the dribble ability Male Basketball Team of SMPN 6 Pekanbaru. The Data collection techniques obtained from the pre-test and post test. The instrument in this research used the Dribbling Test as a tool to measure the ability of Dribbling the ball. The analysis is carried out using the t-test. Based on the data analysis and discussion, it can be concluded that there is a significant effect of the Dribbling Excercise toward the dribbling ability on the Male Basketball Team at SMPN 6 Pekanbaru. It is shown that by T count of 7.8 and T table 1.79. Means T count > T table. At the level of ɑ = 0.05.Keywords : Beranting Dribbling, Dribble , Dribbling Test